Sustainable socio-environmental management in the Ixil community of Chel, Chajul, El Quiché Guatemala. Case study: hydroelectric community - Cruz Herrera, Candelario Elías (2018)
Socio-environmental management serves as a diagnostic and planning tool for the resolution of socio-environmental problems, based on objectives, standards, programs, strategies, methodologies, information, and education. The objective of this paper is to describe and analyze water management, administration, conservation, and use to generate energy by building a hydroelectric plant in the Ixil community, in Quiché, Guatemala, where local experience has shown social, economic, and environmental success. The methodology used a qualitative descriptive approach and analyzed, through workshops with focal groups, the effect of natural resource management in the resulting development in the community. The results identified that the hydroelectric power plant takes advantage of the water potential of the Xesayí Creek. Energy is generated from a run-of-the-river plant with a nominal power of 165 KW and an annual energy production of 1,23 MWh/year. The energy supply benefits 1,566 families from 10 communities in the municipality of Chajul. The environmental management instruments that ensured the success of the community plant were the environmental impact assessment, population participation, and education; these linked axes achieved favorable economic, social, cultural, and environmental impacts. Management, conservation, and use of natural resources are described here, which provide a better lifestyle and the communities’ ability to govern themselves.